Konvergenz gegen logarithmische Verteilungsgesentze - Bakštys, A. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. Бакштис. Сходимость к логарифмическим законам распределенияA. Bakštys. Konvergavimas prie logaritminių pasiskirstymo dėsnių